2018
DOI: 10.1002/chem.201801809
|View full text |Cite
|
Sign up to set email alerts
|

Dual Roles of Li3N as an Electrode Additive for Li‐Excess Layered Cathode Materials: A Li‐Ion Sacrificial Salt and Electrode‐Stabilizing Agent

Abstract: Li CO -passivated Li N with high stability is prepared by aging Li N powder in dry air, and is then used as an electrode additive for a Li(Li Ni Co Mn )O (LLMO) cathode material. The material shows a large irreversible capacity of 800 mA h g during the first charge, with the formation of a Li N intermediate product. Acting as a Li sacrificial salt for a LLMO(+)/graphite(-) Li-ion battery, 2 wt % Li N results in a 10 % increase in discharge capacity. The Li N intermediate product reacts with the electrolyte, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 25 publications
0
31
0
Order By: Relevance
“…However, the Liquid-Li 3 N-DMF and Solid-Li 3 N-DMF ( Fig. 2f) have no difference with DMF and Li 3 N. It further confirmed that there might be no reactions occurred between Li 3 N and DMF, due to the super sensitivity of FT-IR method [37]. The FT-IR spectrum of Solid-Li 3 N-DMSO is shown in the Fig.…”
Section: Resultsmentioning
confidence: 59%
“…However, the Liquid-Li 3 N-DMF and Solid-Li 3 N-DMF ( Fig. 2f) have no difference with DMF and Li 3 N. It further confirmed that there might be no reactions occurred between Li 3 N and DMF, due to the super sensitivity of FT-IR method [37]. The FT-IR spectrum of Solid-Li 3 N-DMSO is shown in the Fig.…”
Section: Resultsmentioning
confidence: 59%
“…After 200 cycles, the discharge capacities of the samples NCM, PPy1, PPy3, PPy5 and PPy7 are 76, 74, 105, 128 and 98 mA h g −1 , corresponding to a capacity retention ratio of 41.1%, 38.5%, 55.5%, 67.2% and 56.3%, respectively. Previous reports have shown that highly acid HF generated from the decomposition of the electrolyte during charge‐discharge process can erode the surface of cathode materials to destroy the surface structure of electrode, resulting in a poor cycling performance . In present investigation, PPy as a protective layer coated on the surface of cathode can effectively prevents the surface from the direct exposing to the electrolyte and corroding by HF.…”
Section: Resultsmentioning
confidence: 72%
“…Sacrificial salts (e.g., azides, oxocarbones, dicarboxylic acids, or hydrazides) contain oxidizable anions that lose electrons during the first charge, forming Li + donors and gaseous species (e.g., CO, CO 2 , or N 2 ) amounting to ≈70% of the salt weight. In spite of the promising improved potential ranges 3–4.5 V versus Li + /Li, the uncontrolled evolution of gases could potentially damage the battery.…”
mentioning
confidence: 99%